2022
DOI: 10.2306/scienceasia1513-1874.2022.053
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of cannabis extract (Cannabis sativa L. subsp. indica (Lam.)) against canine skin infection bacterium Staphylococcus pseudintermedius

Abstract: Superficial bacterial skin infections caused by Staphylococcus pseudintermedius are common in dogs. The cannabis plant has shown potential antibacterial effects, but there is limited information about anti-S. pseudintermedius activity. This study investigated the antibacterial activity of the ethanolic extract and the topical formulations of Cannabis sativa L. subsp. indica (Lam.) against 23 S. pseudintermedius isolates obtained from canine pyoderma using broth microdilution and time-kill assays. The cannabis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Time kill kinetics assay has also indicated that the antibacterial activity of C. sativa ethanolic extract was time dependent and not concentration dependent, the results of the same study revealed that the exposure to the EtOH extract for 3 h caused a 99% death of bacterial cell. While bacterial exposer for about 24 h to EtOH extract induce the death of 99.99% of S. pseudintermedius ATCC 4905 [ 76 ]. A study performed by Skala et al, (2022) on C. sativa extracts (ethanolic, buthanolic and dimethyl ether extracts) obtained from forbidden fruits and cholocope.…”
Section: Antimicrobial Properties Of C Sativa and ...mentioning
confidence: 99%
“…Time kill kinetics assay has also indicated that the antibacterial activity of C. sativa ethanolic extract was time dependent and not concentration dependent, the results of the same study revealed that the exposure to the EtOH extract for 3 h caused a 99% death of bacterial cell. While bacterial exposer for about 24 h to EtOH extract induce the death of 99.99% of S. pseudintermedius ATCC 4905 [ 76 ]. A study performed by Skala et al, (2022) on C. sativa extracts (ethanolic, buthanolic and dimethyl ether extracts) obtained from forbidden fruits and cholocope.…”
Section: Antimicrobial Properties Of C Sativa and ...mentioning
confidence: 99%
“…Ointment formulations are topical drugs that have very good skin adhesion properties and also act to hydrate the skin by protecting it from water loss. Good adhesion to the animal's skin allows the drug to remain active and last for a long time in the lesion site [33,34]. The lipophilic properties of ointment bases make them compatible with lipophilic active plant compounds and promote their antimicrobial and antioxidant activities.…”
Section: Discussionmentioning
confidence: 99%
“…The time-kill test was conducted previously described by Aiemsaard et al . [ 12 ], with some modifications. Briefly, 900 μL of the diluted essential oil was thoroughly mixed with 100 μL of bacterial suspension to give final concentrations of 1, 5, 10, and 20× MIC.…”
Section: Methodsmentioning
confidence: 99%
“…The antibacterial effects of the essential oil spray formulations were determined by the time-kill test [ 12 ]. Briefly, 900 μL of post-milking teat spray and 100 μL of bacterial suspension were mixed thoroughly.…”
Section: Methodsmentioning
confidence: 99%